Case Report: Diagnostic challenges in cervical small cell neuroendocrine carcinoma of a reproductive-age woman - Du, Yitong; Yang, Huiling; Feng, Yichen; Wu, Zejun; Li, Mengyao; Zhu, Tingting; Zhuang, Yali (Frontiers in Oncology, 2025)
Small cell neuroendocrine carcinoma of the cervix (SCNEC) is a rare and highly aggressive malignancy with a poor prognosis. We report the case of a 36-year-old nulliparous woman with a history of HPV-18 infection and repeated cytology showing atypical squamous cells of undetermined significance (ASC-US), while multiple biopsies remained negative. She initially underwent surgery for multiple uterine leiomyomas and severe endometriosis. Ten months later, she presented with acute pelvic pain, rectal pressure, and minor vaginal bleeding. Combined hysteroscopy and laparoscopy revealed suspicious lesions, and histopathology with immunohistochemistry confirmed International Federation of Gynecology and Obstetrics (FIGO) stage IVB SCNEC. Postoperatively, she received platinum-based chemotherapy followed by salvage immunotherapy. Despite a transient decline in tumor markers, the disease progressed rapidly, with enlargement and confluence of pelvic lesions and extensive bone metastases, ultimately resulting in death from multiorgan failure. This case highlights the diagnostic challenges, early systemic dissemination, and poor outcomes of SCNEC, underscoring the urgent need for more effective therapeutic strategies.